2013
DOI: 10.12988/asb.2013.3624
|View full text |Cite
|
Sign up to set email alerts
|

Organic-solvent and surfactant tolerant thermostable lipase, isolated from a thermophilic bacterium, geobacillus thermodenitrificans IBRL-nra

Abstract: Lipases (triacylglycerol acylhydrolase, EC 3.1.1.3), catalyze the hydrolysis of long-chain triglycerides with the formation of diacylglyceride, monoglyceride, glycerol and fatty acids. Lipases are actively used in various industries which include food and diary, pharmaceuticals, organic synthesis and detergent and cosmetics. Thermostable lipases are commercially significant for their potential use in industries as it is stable and active in organic solvents and resistance to high temperature and chemical denat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…In addition, Na 2 HPO 4 at lower level was used at optimized medium. These results agreed somewhat with the previous researches (Balan et al 2013;Burkert et al 2004;Cheng et al 2011;Ebrahimpour et al 2008;Gupta et al 2007;Mahanta et al 2008;Mehta et al 2012). The reason for the difference between various reports is probably due to the characteristic of the each strain.…”
Section: Response Surface Methodologysupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, Na 2 HPO 4 at lower level was used at optimized medium. These results agreed somewhat with the previous researches (Balan et al 2013;Burkert et al 2004;Cheng et al 2011;Ebrahimpour et al 2008;Gupta et al 2007;Mahanta et al 2008;Mehta et al 2012). The reason for the difference between various reports is probably due to the characteristic of the each strain.…”
Section: Response Surface Methodologysupporting
confidence: 91%
“…Generally, biomass and lipase production is enhanced by sources containing nitrogen especially organic nitrogen sources, which supply powerful source of nitrogen for the growth of bacteria and increases their yields of proteins. These findings confirm relevant data reported in similar studies (Balan et al 2013;Burkert et al 2004;Cheng et al 2011;Ebrahimpour et al 2008;Mahanta et al 2008;Mehta et al 2012;Zaliha et al 2006).…”
Section: Preliminary Optimization Using "One-variable-at-a-time"supporting
confidence: 92%
See 1 more Smart Citation
“…Polar solvents having LogP value less than 2 cause enzyme inactivation because they compete with the enzyme for water molecules. Therefore, water is removed from the enzyme causing protein unfolding, making it unstable [31]. Y. lipolytica is known to have 16 different putative lipase genes, out of which YLIP2 is the main extracellular lipase and most studied one.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the cases, it has been reported that solvents having LogP value less than 2 result in enzyme inactivation. The polar solvents compete with the enzyme for water molecules and thus strip off water from the enzyme leading it to unfold and making it unstable [24]. Interestingly, a very different property was observed for ZZ-YLIP9 in that it was more stable as well as its activity was highly enhanced in the presence of solvents with logP less than 0.05, i.e., very hydrophilic solvents (2-propanol, ethanol, acetone, 1,4-dioxane).…”
Section: Thermostability and Solvent Stabilitymentioning
confidence: 99%